Reversal of Anthropocentric Worldview in Margaret Atwood’s Oryx and Crake - Sharma, Prakash (Tribhuvan University Journal, 2023)
Anthropocentric worldview is the main cause of the ecological problems that the world is confronting at present. This study explores and analyze how Margaret Atwood’s Oryx and Crake reveals the reversal of the anthropocentric worldview as the only solution of the ecological problems caused by human centric worldview by employing eco critical insights envisioned by Lawrence Buell. The study scrutinize the way our rationality rejects the subjectivity of nature and regards it as subordinate to human beings in the novel. Therefore, there is a strong need to change our worldview. It follows qualitative research design and uses critical, analytical and interpretative methods for interpreting textual data. Critically analyzing different events and situations that highlight the ugliness and cruelty caused by human-centered activities, it emphasizes people’s indifference towards the autonomy of the natural world. Similarly, it critiques the selfish modification of natural components as per human need. Such actions have paved the path for apocalyptic events. Human beings can avoid such events by changing their anthropocentric worldview and making it more eco centric. This research exposes the way Atwood blames anthropocentric worldview as the main cause of the environmental crisis of present time. Self-centric corporate greed and uncontrolled bioengineering give birth to different ecological and biological problems. These problems lead the world to the possible apocalypse that results in the extinction of the existence of all the beings and things of the ecosphere. This study recommends immediate action to protect our ecosphere respecting the interdependence between human and natural world. Ecocentric worldview only guarantees the survival of all on this earth enjoying intrinsic values.